Fools: From marvels of nature to asylum inmates. Imaginations of natural folly - Ruth von Bernuth (Disability Studies Quarterly, 2006)
In medieval and Renaissance times European courts kept fools, who were placed into one of two categories: artificial fools (or jesters) and natural fools. The present study examines natural fools. Extant studies generally treat natural fools as both mentally and physically ill and/or disabled. This study contributes to the discussion of natural folly by examining two sources about the Ernestinian Saxon court fool Claus Narr. According to the documents natural fools were seen as permanently mentally changed people and classified as so-called "wonder men." Therefore they were kept and collected at courts. When permanent mental difference and psychiatric disease amalgamated at the beginning of the 18th century, however, the natural fool became an object of education and medicine. This paper argues that the changing meaning of the natural fool nevertheless retained components of its initial medieval conception.